2015
DOI: 10.1186/s12967-015-0540-y
|View full text |Cite
|
Sign up to set email alerts
|

Severe disturbance of glucose metabolism in peripheral blood mononuclear cells of schizophrenia patients: a targeted metabolomic study

Abstract: BackgroundSchizophrenia is a widespread and debilitating mental disorder. However, the underlying molecular mechanism of schizophrenia remains largely unknown and no objective laboratory tests are available to diagnose this disorder. The aim of the present study was to characterize the alternations of glucose metabolites and identify potential diagnostic biomarkers for schizophrenia.MethodsGas chromatography/mass spectrometry based targeted metabolomic method was used to quantify the levels of 13 glucose metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 41 publications
3
30
0
1
Order By: Relevance
“…Recently, glucose regulation and energy metabolism have emerged as major players in neurological disease and specifically in dopaminergic disorders. Glycolysis pathway disruption has been identified in PBMCs from schizophrenic patients and analysis of serum metabolites in patients with restless legs syndrome (RLS) showed several dysregulated pathways, including increased lactate in both RLS and PD . Vascular degeneration has also been observed in PD brain tissue .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, glucose regulation and energy metabolism have emerged as major players in neurological disease and specifically in dopaminergic disorders. Glycolysis pathway disruption has been identified in PBMCs from schizophrenic patients and analysis of serum metabolites in patients with restless legs syndrome (RLS) showed several dysregulated pathways, including increased lactate in both RLS and PD . Vascular degeneration has also been observed in PD brain tissue .…”
Section: Discussionmentioning
confidence: 99%
“…Both increased and decreased levels of lactate (plasma (Cai et al, 2012); PBMCs (Liu et al, 2015); serum (Xuan et al, 2011); urine & serum (Yang et al, 2013)) and taurine (plasma (Bjerkenstedt et al, 1985); urine (Cai et al, 2012)) have also been reported in patients. Consistent findings have included reduced levels of urine, and serum α-Ketoglutarate (Xuan et al, 2011;Yang et al, 2013), increased levels of PBMC and serum pyruvate (Liu et al, 2015;Yang et al, 2013) and increased PBMC and serum glycerol (Liu et al, 2014;Xuan et al, 2011). In the study by Cai et al (Cai et al, 2012) negative correlations between urinary α-ketoglutarate and PANSS negative scores were reported.…”
Section: Carbohydrate Metabolism and Other Organic Acids And Derivativesmentioning
confidence: 97%
“…Reduced levels of citrate (in urine, plasma, PBMCs and serum) are reported in the majority of studies (Cai et al, 2012;Liu et al, 2015;Xuan et al, 2011;Yang et al, 2013), however Yang et al (Yang et al, 2013) reported both increased serum citrate and reduced urine citrate concentrations in schizophrenia patients. Glucose (PBMC, serum and urine levels) was mainly reported as being increased in schizophrenia patients (Cai et al, 2012;Liu et al, 2015;Xuan et al, 2011;Yang et al, 2013) however Cai et al (Cai et al, 2012) found increased urinary concentrations but decreased plasma concentrations in schizophrenia patients. Both increased and decreased levels of lactate (plasma (Cai et al, 2012); PBMCs (Liu et al, 2015); serum (Xuan et al, 2011); urine & serum (Yang et al, 2013)) and taurine (plasma (Bjerkenstedt et al, 1985); urine (Cai et al, 2012)) have also been reported in patients.…”
Section: Carbohydrate Metabolism and Other Organic Acids And Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“… ðàáîòå M.L. Liu et al (2015) áûëî ïîêàçàíî, ÷òî ïðè øèçîôðåíèè èçìåíåíèÿ ìåòàáîëèòîâ â îñíîâíîì ñâÿçàíû ñ îáìåíîì àöèëêàðíèòèíîâ, ëèïèäíûì îáìåíîì è ìåòàáîëèçìîì òðèïòîôàíà, ÷òî ïðèâîäèò ê êîìáèíàöèè áèîìàðêåðîâ, âêëþ÷àþùèõ àöèëêàðíèòèí Ñ10:1 è òðèïòîôàí [40]. Àíàëèç ñïåêòðà 29 àöèëêàðíèòèíîâ â ïëàçìå êðîâè 225 áîëüíûõ øèçîôðåíèåé è 175 çäîðîâûõ ëþäåé, ñîïîñòàâèìûõ ïî âîçðàñòó è ïîëó, ïîêàçàë çíà÷èòåëüíî áîëåå âûñîêèå óðîâíè C4-OH (C3-DC) è C16:1, íà ôîíå íèçêèõ êîíöåíòðàöèé C3, C8, C10, C10:1, C10:2, C12, C14:1-OH, C14:2 è C14:2-OH ó áîëüíûõ øèçîôðåíèåé ïî ñðàâíåíèþ ñî çäîðîâûìè ëèöàìè [41].…”
Section: изучение роли аминокислот и ацилкарнитинов в патогенезе шизоunclassified